A new species of Thinouia (Paullinieae, Sapindaceae) from the Amazon and its phylogenetic placement - Medeiros, Herison (PhytoKeys, 2020)
Thinouia is a Neotropical genus of lianas with approximately 12 species and is the only genus in tribe Paullinieae with actinomorphic flowers. During a taxonomic revision of the genus and fieldwork in south-western Amazonia, we found a new species that appears similar to Thinouiatrifoliata (ex Allosanthus) because of its racemiform inflorescence. However, before describing the new species, we had to confirm that Allosanthus was congeneric with Thinouia so we could place the new species in the correct genus. The results of the phylogenetic analysis, based on molecular data (trnL intron and ITS sequences), show that Allosanthus should be included in Thinouia. Thus, the new taxon is described here as Thinouiacazumbensissp. nov. The new species is described, illustrated and phylogenetic trees showing relationships within supertribe Paulliniodae and Thinouia and the congeneric Allosanthus are given.